MEKANISME PARTISIPASI MASYARAKAT DALAM PEMBENTUKAN PERATURAN DAERAH DI KABUPATEN INDRAGIRI HULU - Kevin Destra Volta; Mexsasai Indra; Zainul Akmal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The aim of this research is to find out the mechanism of communityparticipation in the formation of regional regulations in Indragiri Hulu Regency. Andto find out the arrangement of regulations related to community participation in theformation of regional regulations in Indragiri Hulu Regency. The data sourcesneeded to obtain information were the Legal Section of the Regional Secretariat ofIndragiri Hulu Regency, the Public Relations Section of the Indragiri Hulu RegencyDPRD, the Head of the Special Committee and members in the Raperda Discussion inIndragiri Hulu Regency and community representatives in making regionalregulations of Indragiri Hulu Regency. The data collection tools for this research arefield research studies or interviews and document studies (library). The research datawere analyzed using qualitative data analysis.The type used in this research is descriptive analysis. Research usingdescriptive analysis is research that merely describes the state of objects or eventswithout an intention to draw general conclusions. Legal research can be carried outusing 2 (two) approaches, which consist of normative legal research (normativejuridical) and sociological legal research (empirical juridical). So it can beconcluded for this research that leads to an empirical juridical research approach.From the research results it is known that public participation is viewed fromthe applicable laws and regulations, namely Article 136 paragraph 4, Article 139paragraph 1 Number 23 of 2014 concerning Regional Government, Article 53 of theLaw of the Republic of Indonesia Number 13 of 2022 concerning the SecondAmendment to Law Number 12 of 2011 concerning the Establishment of Legislation.Forms of community participation can be done verbally and/or in writing. Theproblem for Indragiri Hulu Regency is that online community participation is not yetavailable..Keywords: Community Participation, Formation Of Local Regulations